2021
DOI: 10.1029/2021gl095740
|View full text |Cite
|
Sign up to set email alerts
|

Global Impact of Lightning‐Produced Oxidants

Abstract: Lightning plays a major role in tropospheric oxidation chemistry (Murray et al., 2013). It can produce nitrogen oxides, hydrogen oxides, and ozone through electrical discharges in the atmosphere. Electric discharges in gases have three regions, the dark discharge, glow discharge, and arc discharge, with voltage building up during the first two regions before suddenly dropping during the last region because of neutralization (National Research Council, 1986). We refer these three regions respectively as the sub… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 55 publications
0
9
0
Order By: Relevance
“…
As a long-distance discharge phenomenon in nature, lightning not only poses serious risks to human beings but causes wildfires as well, which in turn affect the evolution of species and ecosystems (He et al, 2022;Hessilt et al, 2022). Lightning is the only natural source of nitrogen oxides (NOx) in the troposphere which regulates the oxidation ability in the upper troposphere and modulates tropospheric chemistry (Brune et al, 2021;Mao et al, 2021).Lightning activity shows large spatial heterogeneity on the globe with several lightning chimney regions around the equator (
…”
mentioning
confidence: 99%
“…
As a long-distance discharge phenomenon in nature, lightning not only poses serious risks to human beings but causes wildfires as well, which in turn affect the evolution of species and ecosystems (He et al, 2022;Hessilt et al, 2022). Lightning is the only natural source of nitrogen oxides (NOx) in the troposphere which regulates the oxidation ability in the upper troposphere and modulates tropospheric chemistry (Brune et al, 2021;Mao et al, 2021).Lightning activity shows large spatial heterogeneity on the globe with several lightning chimney regions around the equator (
…”
mentioning
confidence: 99%
“…In Earth's atmosphere, the production of NO affects ozone photochemistry (Crutzen 1970) and the lifetimes of a range of other gases, e.g. CO and nitrous oxide (N 2 O) (Rakov & Uman 2003;Brune et al 2021;Mao et al 2021). As the air cools rapidly, the abundances from the high-temperature reactions are 'frozen in' via the so-called Zel'dovich mechanism (Zeldovich et al 1947).…”
Section: Emissions Of No From Lightningmentioning
confidence: 99%
“…10.1029/2023JD039362 2 of 12 HO x based on a global modeling study (Mao et al, 2021). Altogether, these studies have concluded that LHO x generated in thunderstorms potentially account for 0.3%-16% of global OH and LHO x generated by a variety of electrical discharge types and strengths could create 2-4 orders of magnitude more HO x locally or regionally relative to other HO x sources.…”
mentioning
confidence: 94%
“…Subsequent laboratory experiments confirmed that this electrically generated HO x (LHO x ) was real, that it can be generated in both sparks and weak, invisible discharges called subvisible discharges, and it has a longer lifetime than expected in spark discharges (Jenkins et al., 2021). Additional studies have demonstrated prodigious LHO x production in corona discharges (Brune et al., 2022; Jenkins et al., 2022) and LHO x has also been found to be a possibly significant source of atmospheric HO x based on a global modeling study (Mao et al., 2021). Altogether, these studies have concluded that LHO x generated in thunderstorms potentially account for 0.3%–16% of global OH and LHO x generated by a variety of electrical discharge types and strengths could create 2–4 orders of magnitude more HO x locally or regionally relative to other HO x sources.…”
Section: Introductionmentioning
confidence: 99%